Between Cosmopolitan Ideals and State Sovereignty Studies in Global Justice - Tinnevelt, R.; Verschraegen, G.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
Between Cosmopolitan Ideals and State Sovereignty explores how philosophers and political theorists have recast principles of justice and human rights in the light of challenges posed by globalization. It discusses ethical issues that arise at a global level and considers whether human rights and sovereignty can ever be reconciled.
Keywords: Political theory; Political philosophy; Social justice; Human rights; Private international law; Conflict of laws; Political science; Political Theory; Political Philosophy; Social Justice, Equality and Human Rights; Human Rights; Private International Law, International & Foreign Law, Comparative Law .; Political Science